Isolation of Potential Extracellular Cellulase Producer and Determination of Cellulase Production Efficiency with Various Raw Substrates: Life Sciences-Microbiology for health care - Patel, Nimisha; Gangawane, Ajit K (International Journal of Life Science and Pharma Research, 2021)
Cellulase is one of the important groups of enzyme for many industrial applications. It is applied in various processes of food industries, paper and pulp industry, fabric industry, medicine and pharma industry, agriculture industries etc. Microorganisms are among the most potential source for large scale production of this enzyme. The current study is aimed to isolate microorganisms which are capable of producing cellulase and to determine its efficiency for production of cellulase with different raw materials. For this study, bacteria microorganisms were isolated on CMC containing media. Screening was done using congo red (0.1%) and NaCl (1%) solution. Among various isolated species, Bacillus amyloliquefaciens was identified as the most potential strain and hence selected for further study, various raw materials which are rich in cellulose were used for cellulase production. These raw materials were sugarcane bagasse, paper pulp, molasses, orange peel, wheat bran, cassava waste, tea waste and agriculture waste. Cellulase activity was determined by using dinitrosalicylic acid (DNSA) method. Results of the study have shown that among all the raw materials, sugarcane bagasse, molasses and paper pulp were found as the most potential sources for enzyme production. DNSA have shown 0.97 IU/mL, 0.98IU/mL and 0.88 IU/mL of enzyme activity respectively for all the three raw materials. Results have also shown that agriculture waste alone is not found suitable for production of cellulase as it has shown only 0.32 IU/mL of enzyme activity. From the entire study, it was concluded that for large scale production of cellulase, sugarcane bagasse and molasses are the best sources using Bacillus amyloliquefaciens.